Mysis nordenskioldi n. sp. (Crustacea, Mysida), a circumpolar coastal mysid separated from the NE Pacific M. litoralis (Banner, 1948) - Audzijonyte, A; Vainola, R (Polar Biology, 2007)
Mysis nordenskioldi n. sp. is a circumpolar, arctic-subarctic coastal mysid crustacean, earlier considered conspecific with M. litoralis (Banner, 1948) and in the past also confused with the circumpolar M. oculata (Fabricius, 1780 ). Mysis litoralis itself seems to be restricted to the northeastern North Pacific. Formal diagnoses and descriptions of the three species are here given based on morphological and molecular characters (allozymes, mtDNA). The species are morphologically distinguished by features of the telson and by the setation of maxillae and maxillipedes. Molecular differences diagnosing M. nordenskioldi from the two others were found at seven to eight allozyme loci, while M. oculata and M. litoralis differed from each other at five loci. In mitochondrial DNA, M. nordenskioldi is distinguished from the others by 8% nucleotide divergence, whereas M. litoralis and M. oculata make an inseparable cluster (<1%), suggesting post-speciation mitochondrial introgression. Initial phylogeographic data on M. nordenskioldi and M. oculata are presented. A morphological key to marine Mysis species is given.